Fuzzy Logic Control in ATM Network - Lau, Weng Tat; Phang, K. K.; Yaacob, Mashkuri; Ling, T. C. (Malaysian Journal of Computer Science, 1999)
Due to the unpredictable behavior of the traffic and various traffic characteristics, it has become a great challenge for ATM networks to effectively control traffic and congestion while at the same time provide the desired quality of service. In this paper, a fuzzy logic traffic controller is proposed to perform traffic and congestion control functions. Simulation results showed the feasibility of utilizing fuzzy logic control in an ATM network.